2021
DOI: 10.3390/biomedicines9091179
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Relevance of Circulating Tumor Cells in Prostate Cancer Management

Abstract: Given the low specificity of the routinely used biomarker prostate-specific antigen, circulating tumor cell (CTC) enumeration seems to be particularly useful in the monitoring of prostate cancer. In this review, we focused on a few aspects of CTC enumeration in prostate malignancies: prognostic value in metastatic and non-metastatic tumors, role in the monitoring of treatment outcomes, use as a surrogate marker for survival, and other applications, mostly for research purposes. CTC enumeration, without a doubt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 103 publications
(179 reference statements)
0
16
0
Order By: Relevance
“…In recent years, the high incidence and mortality of PCa have caused worldwide concern ( 41 , 42 ). The diagnosis and prognosis of PCa are currently determined by tissue biopsy and PSA levels ( 42 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, the high incidence and mortality of PCa have caused worldwide concern ( 41 , 42 ). The diagnosis and prognosis of PCa are currently determined by tissue biopsy and PSA levels ( 42 ).…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, the high incidence and mortality of PCa have caused worldwide concern ( 41 , 42 ). The diagnosis and prognosis of PCa are currently determined by tissue biopsy and PSA levels ( 42 ). However, tissue biopsy is invasive, and the predicted accuracy of PSA should be furthermore improved.…”
Section: Discussionmentioning
confidence: 99%
“…Historically, the use of prostate specific antigen (PSA) and other blood based biomarkers have produced risk models with only moderate calibration and discrimination in the metastatic prostate cancer setting (Gafita et al 2021). As a result, exploring informative new biomarkers continues, with a recent focus around circulating tumor cells and serum testosterone (Cieslikowski et al 2021;Ryan et al 2019).…”
Section: Prostate Cancer Datamentioning
confidence: 99%
“…It is currently recognized that the existence of CTCs is one of the main reasons for tumor recurrence or metastasis. Studies have demonstrated the prognostic value of CTCs testing in breast, lung, and prostate cancers [ 6 8 ]. Abnormally alternating (decreased or increased) chromosomes in cells are well-recognized markers of malignancy, studies have found that aneuploid karyotypes in CTCs can help explore cancer prognosis and treatment efficacy [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%